Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Can someone help me simplify this boolean expression? $$(a+b+c+d)(a'+b'+c'+d')$$

so if I use the distributive property, I'll get:

$$ab'+ac'+ad'+ba'+bc'+bd'+ca'+cb'+cd'+da'+db'+dc'$$

I'm stuck after this step...

share|improve this question
4  
At least tell us what the problem is! Duh! –  anon Feb 4 '12 at 2:27
1  
I assume the result asks you to simplify the expression. $a+b+c+d=0$ exactly when $a=b=c=d=0$. $a'+b'+c'+d'=0$ exactly when $a=b=c=d=1$. In all other cases, both sums have value $1$. So when is their product $1$? –  Dilip Sarwate Feb 4 '12 at 2:36
add comment

1 Answer

Dilip’s hint is good. Alternatively, if you know the de Morgan’s laws, you can observe that $$a'+b'+c'+d\,'=(abcd)'$$ and $$a+b+c+d=(a'b'c'd\,')'\;,$$ so that $$(a+b+c+d)(a'+b'+c'+d\,')=(a'b'c'd\,')'(abcd)'\;.\tag{1}$$ Now use de Morgan again to get rid of the outer negations on the righthand side of $(1)$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.